Pengaruh Kompensasi dan Motivasi Kerja Terhadap Turnover Intention Melalui Stress Kerja Karyawan PT. Bank Tabungan Negara Kantor Cabang Semarang - Malna, Muhammad Afrizal; Rodhiyah, Rodhiyah; Dewi, Reni Shinta (Departemen Administrasi Bisnis, FISIP Universitas Diponegoro, 2015)
This research aims to know the influence of the compensation and work motivation toward turnover intention through work stress of employee’s of PT. Bank Tabungan Negara branch office semarang. This type of research is explanatory, to explain the causal relationship between the compensation and work motivation toward turnover intention. Population ini this research is PT. Bank Tabungan Negara branch office semarang permanent employee’s. The number of samples in this study amounted to 91 people used by census sampling’method. Data collection methods used is literature studies and questionnaires. The data obtained were analyzed using a test of validity, reliability, simple linear regression and multiple linear regression. While hypothesis testing using t-test, F test and path analysis. The results showed that compensation and work motivation affects turnover intention. Based on the path analysis, its show that direct effect of compensation toward turnover intention is 0,451. Meanwhile, the impact of compensation toward turnover intention through work stress is 0,518. Its show that the impact of compensation towardbturnover intention is higher if through work stress. In the other side, the direct effect of work motivation toward turnover intention is -0,199. Menawhile, the impact of work motivation toward turnover intention through work stress is -0,517. Its show that the impact of work mtoviation toward turnover intention is higher if through work stress. Conclusion the study show compensation, work motivation and work stress partially and simultaneously affect turnover intention. Firms need to review standards and employment targets , reviewing the reward and punishment system , improving employee discipline and working relationships both vertically and horizontally and create a working environment that is conducive to both physical and non-physical.